Roland Barthes: Recollections in Gratitude - Leon S. Roudiez (Studies in 20th & 21st Century Literature, 1981)
An informal homage in which I recall personal and professional encounters with Roland Barthes and his texts over a period of some twenty-five years, during which I developed increasing respect for the man and interest in his critical practice.
Keywords: Roland Barthes; homage; personal experience